2015
DOI: 10.1007/s00404-015-3823-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of angiogenesis modulators in pregnant women with pre-eclampsia: a case–control study

Abstract: Serum PlGF levels were reduced in the pregnant women with PE and were unrelated to disease severity. Serum levels of VEGF, IL-17, IL-10 and TNF-α were reduced in the pre-eclamptic pregnant women when compared with their normotensive peers, without statistically significant differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 39 publications
2
6
0
2
Order By: Relevance
“…The role of IL‐6 in placental invasiveness during implantation has been described previously, but results regarding IL‐6 levels in preeclampsia patients are rather controversial . Recent studies have not observed differences in IL‐6 levels between preeclampsia and uncomplicated pregnancies, which is in agreement with our results.…”
Section: Discussionsupporting
confidence: 92%
“…The role of IL‐6 in placental invasiveness during implantation has been described previously, but results regarding IL‐6 levels in preeclampsia patients are rather controversial . Recent studies have not observed differences in IL‐6 levels between preeclampsia and uncomplicated pregnancies, which is in agreement with our results.…”
Section: Discussionsupporting
confidence: 92%
“…In our exploratory analysis, IL6 was associated with preeclampsia but only in white women. Overall, we found few associations between systemic immune markers and preeclampsia in second trimester samples which is consistent with other mid-trimester investigations [11, 12]. Thus, second trimester serum immune markers may have little use for prediction of preeclampsia.…”
Section: Discussionsupporting
confidence: 88%
“…A second trimester study has reported lower circulating IL10, TNF-α and IFN-γ among women who develop preeclampsia [10]. While others report no significant differences in circulating immune markers [11, 12]. First trimester investigations are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, two case‐control studies with 55 and 80 women. respectively, investigating serum levels in the third trimester, found no significant association of IL‐17 with the disease …”
Section: Resultsmentioning
confidence: 98%